Profile of the Physical Condition of Bali Tennis Athletes in 2020 - I Komang Sukarata Adnyana (Gelanggang Pendidikan Jasmani Indonesia, 2021)
This research aims to provide knowledge and information about the physical condition of provincial tennis athletes in bali men's category by 2020. This type of research is a survey by conducting a live physical condition test. The data obtained is analyzed in accordance with the standards of Pratama athletes. Based on the results of the analysis of physical condition tests, the percentage of the physical condition of male athletes who have met the fitness standard is 64.48% and who do not meet the fitness standard is 35.52%, so in general the physical condition of the male category athlete is classified quite well according to the physical condition conversion table is in the range of 60% to 69%. The conclusion is that the physical condition of Porprov Bali athletes in the 2020 men's tennis category is quite good.